Experimental study on seismic control of towers in cable-supported bridges by incorporating fluid viscous dampers between sub-towers. Issue 10 (July 2020) - Zhou, Peng; Liu, Min; Li, Suchao; Li, Hui; Song, Gangbing
In this article, the seismic control of towers incorporated with fluid viscous dampers between sub-towers is investigated experimentally. To replace one entire tower, an alternative scheme consisting of four separate sub-towers is first proposed. Fluid viscous dampers are utilized as energy dissipation devices to be installed between sub-towers. Experimental tests are conducted to study the damping force characteristics. Three control strategies with various distributions of these dampers between sub-towers are developed. Then, a series of shaking table tests are carried out to evaluate the control performance of the proposed control strategies. Different earthquake records are adopted as seismic loadings. Experimental results clearly show a remarkable reduction in the towers seismic responses, including the accelerations, relative displacements, and strains. Rather than attaching dampers in concentrated ways, the strategy of distributing dampers uniformly behaves better.